Pests and diseases incidence at different growth stages of Melon Manis Terengganu - Natasya Amirah Tahir; Nur Aida Hashim; Abdul Manaf Tahir; Wahizatul Afzan Azmi (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
Melon Manis Terengganu (MMT) is a newly developed cultivar of Cucumis melo that is exclusively planted in Terengganu and have been recognized as Terengganu’s iconic fruit in 2015. Currently, the occurrence of pests and diseases is one of the major constraints in MMT cultivation. Thus, the study on pest and disease incidence at different growth stages of MMT plants were conducted as very little information about it on MMT has been reported. Collection of pest samples and observation on diseases incidence were conducted for eight weeks following the growth stages of MMT. A total of 176 individuals belonging to six orders, 15 families and 37 species of insects were collected throughout this study. Results revealed that red pumpkin beetle (RPB) (Raphidopalpa foveicollis: Chrysomelidae: Coleoptera) was the most dominant pest found on almost all growth stages of MMT. RPB were recorded in Week 1 until Week 5 with infestation on the MMT leaves and stems that caused severe damage on the plants. The second dominant pest was melon worm (Diaphania hyalinata: Crambidae: Lepidoptera) which was more abundant during foliage expansion stage (Week 3), followed by leaf miner fly (Liriomyza trifolii: Agromyzidae: Diptera) which was mostly found during the fruit maturation stage of MMT plants. A few diseases were recorded from week three until week eight. The most dominant diseases recorded were Cucurbits Yellow Stunting Disorder Virus (CYSDV), Powdery Mildew and Verticillium wilt. Findings from this study may provide important information on pests and diseases of MMT which is the first step in developing effective pest and disease control strategy.